The phrase 'The Great War' in british discourse during world war one - Melia, Paul (2018)
The association of the term ‘The Great War’ with World War One, if it began 100 years ago, could be seen as telling, not only about attitudes at the time (and whether it meant ‘jolly big’ or ‘jolly good’), but about our retrospective attitudes to those who were involved. Through an examination of propaganda, periodicals, political statements and specific pre-war literature, an assumption that as a phrase it is indicative of jingoistic and bellicose hysteria generated by influential politicians for the gullible citizens of whichever participant nation, can be shown as a misleading simplification. Instead, with a concentration on Britain, a study of its use by statesmen such as Asquith and Lloyd George, the very particular circumstances under which it appeared in Punch magazine, and the overt zeal some advocates of war with Germany displayed from several years before 1914, is revealing of very different public standpoints among supporters of the war.